THE LANZO SOUTH PERIDOTITE: MELT/PERIDOTITE INTERACTION IN THE MANTLE LITHOSPHERE OF THE JURASSIC LIGURIAN TETHYS - Piccardo, Giovanni B.; Müntener, Othmar; Zanetti, Alberto; Romairone, Anna; Bruzzone, Stefano; Poggi, Eugenio; Spagnolo, Gianluca (Ofioliti, 2004)
New field, textural, petrologic and geochemical researches on the Lanzo South ophiolitic peridotite constrain the mantle processes which accompanied the geodynamic evolution during rifting and opening of the Ligurian Tethys ocean basin. They reveal the presence of different types of peridotites with variable structural-geochemical characteristics and mutual relationships: (1) “lithospheric” spinel peridotites preserve records of a long residence in the thermal lithosphere, (2) “reactive” spinel peridotites record effects of melt/rock interaction; (3) “impregnated” plagioclase-rich peridotites show significant enrichment of basaltic components (“refertilization”) in the form of mm-size plagioclase-pyroxene-rich veins and pockets. Our present results indicate that the Lanzo South peridotites were accreted to the thermal lithosphere, probably from garnet-peridotite-facies depths, where progressively cooled and completely recrystallized under spinel-peridotite-facies conditions. Subsequently, in response to the pre-oceanic rifting related to the opening of the Ligurian Tethys, lithospheric mantle sections of the Lanzo massif were progressively exhumed to shallow lithospheric levels, whereas the underlying asthenosphere rose and underwent near-adiabatic decompression melting. The resulting fractional melts migrated through and reacted with the overlying extending mantle lithosphere. During initial melting stages of the ascending asthenosphere, fractional melt increments migrated upwards in the lithospheric mantle column via diffuse and reactive porous flow, and caused depletion of the lithospheric mantle by melt/rock interaction (pyroxene dissolution and olivine precipitation), being olivinesaturated but pyroxene-undersaturated. Large areas of pyroxene-depleted, olivine-enriched “reactive” peridotites were thus formed. Subsequently, progressively pyroxene-saturated melts migrated pervasively in the “lithospheric” and “reactive” peridotites; at shallower levels, the competing effects of heating by melt percolation and cooling by ongoing exhumation led to interstitial crystallization of percolating melts, and to progressive clogging of melt channels. This process formed an upper zone of refertilized, “impregnated” plagioclase peridotites, and forced the ascending melts to percolate along focused channels where high melt/peridotite ratios caused the complete dissolution of pyroxenes and the formation of “replacive” spinel dunites. These high-porosity dunite channels allowed “rapid” migration of the first aggregated MORB melts, which were produced in the underlying asthenosphere and escaped melt/rock interaction during upwelling. The rheology of the lithospheric mantle was modified largely by lithosphere-asthenosphere interaction; the lithospheric mantle attained asthenospheric characteristics during erosion by melt percolation. Following continuous upwelling in the thermal lithosphere and increasing conductive heat loss, the thermochemically modified lithospheric mantle returned to more cold and brittle conditions. Later, the Lanzo South peridotites were intruded along fractures by variably fractionated, Mg-rich to Fe-rich magmas deriving from MORB primary melts, most probably aggregated at asthenospheric levels and differentiated in shallow magma chambers. The above evidence reveals a composite magmatic stage recorded in the mantle; percolating melts were trapped in the lithospheric mantle and never reached the surface. This magmatic stage preceded later shallow emplacement of MORB magmas, which formed gabbroic and basaltic rocks of the Jurassic oceanic crust. Records of melt percolation, impregnation and melt/peridotite reaction are common in ophiolitic peridotites and present-day oceanic mantle lithosphere. Relationships between the results obtained for the Lanzo ophiolitic peridotites and those determined for others Alpine-Apennine peridotites, provide a mechanism to explain non-volcanic and volcanic stages during rift evolution of the Ligurian Tethys, and might be equally applicable to modern slow spreading ridges, which are characterized by variable magmatic (volcanic) and amagmatic (non-volcanic) stages.